RAB5B: explore its carcinogenic potential and understand its role, prognostic value and biological significance in pan-cancer - Zhu, Jing; Yu, Chun; Xu, Xin; Zou, Chu; Li, Jiaqi; Wang, Rui; Li, Xinchao; Sun, Aijun; Wang, Shiyan; Jiang, Chao (Frontiers in Immunology, 2025)
BackgroundThe RAB5B protein belongs to the RAB family and is primarily localized to early endosomes. It regulates the endocytic pathway through its GTPase activity, thereby affecting various aspects such as cell signaling and metabolic regulation. Dysfunction of RAB5B is closely associated with the progression and deterioration of multiple types of tumors. Although studies have revealed the functional mechanisms of RAB5B in specific tumor types, its role in pan-cancer and the underlying molecular mechanisms still lack in-depth analysis.MethodsA comparative analysis of RAB5B gene expression was conducted using transcriptomic datasets from Cancer Genome Map (TCGA) and Genotype-Tissue Expression (GTEx), followed by tissue distribution profiling via Human Protein Atlas (HPA) and GeneMANIA to map its expression across human tissues. The TISCH database identified primary cell types expressing RAB5B within the tumor microenvironment, while univariate Cox regression modeling evaluated its prognostic significance in cancer outcomes. Integrative genomic analyses using cBioPortal and Gene Set Cancer Analysis (GSCA) further characterized RAB5B’s genomic alterations and cancer-specific profiles. Gene_DE module 2.0 (TIMER 2.0) deciphered associations between RAB5B expression and tumor-infiltrating immune cell subsets. To elucidate functional mechanisms, Gene Set Enrichment Analysis (GSEA) and Gene Set Variation Analysis (GSVA) identified biological pathways co-regulated with RAB5B, and in silico approaches combining CellMiner with molecular docking predicted interactions between RAB5B and anticancer drugs. In vitro wound healing assays were performed to validate RAB5B’s role in modulating cellular migration dynamics, complementing bioinformatics findings with experimental evidence.ResultsRAB5B protein expression varied significantly across tumors, with different prognostic values. In most malignancies, RAB5B expression correlated positively with Copy Number Variation (CNV) and methylation. It also correlated significantly with immunotherapy biomarkers and responses. ESTIMATE and immune infiltration analyses highlighted RAB5B’s link to immunosuppression, emphasizing its role in immune regulation. Molecular docking and experimental validation showed that downregulating RAB5B inhibited cell proliferation and reduced cancer cell migration.ConclusionOur study revealed the key role of RAB5B in tumor biomarkers. RAB5B inhibits ectopic metastasis of tumor cells mainly by regulating the process of cell adhesion and migration. This discovery is of great significance for developing new anticancer inhibitors.